Generation and use of site-directed chromosomal cyaA’ translational fusions in Salmonella enterica. - Ramos Morales, Francisco; Cardenal Muñoz, Elena; Cordero Alba, Mar; Baisón Olmo, Fernando (Springer, 2015)
CyaA from Bordetella pertussis is a calmodulin-dependent adenylate cyclase. Fusions to the catalytic domain of CyaA (CyaA’) are useful tools to detect translocation of type III secretion system effectors from Gram-negative pathogens like Salmonella enterica. These fusions are usually generated using plasmids with strong promoters. Here, we describe a protocol to insert the CyaA’-encoding sequence in a specific site in the bacterial chromosome in order to get a monocopy fusion whose expression is driven by the native promoter. We also describe the procedure to detect translocation of a CyaA’ fusion into mammalian cells.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Translocación (Genética); Salmonella - Genética; Bacterias gram negativas; Bacterias - Metabolismo; Effectors; Translocation; CyaA; cAMP; Salmonella; Chromosomal translational fusions; Type III secretion